Formulation of Baby Porridge Flour Using Nagara Tuber and Kalakai (Stenochlaena palustris) as Iron Fortifying Agent with Natural Flavor of Ambon Banana - Sholihah, Nitie Ma'rifatus; Nugroho, Ph.D., Agung; Agustina, Lya (Kementerian Perindustrian, 2018)
Kalakai (Stenochlaena palustris) is a fern that lives wildly in nature. High iron content in the diet underlies the use of kalakai plants as a natural iron fortifying food for growing children. The purpose of this study was to determine the best formulation of baby porridge flour meeting the Indonesian National Standard (SNI). Kalakai was selected as a Fe fortifying material due to its high content of Fe. Three formulations (A, B, and C) were produced from three different flours (cassava nagara, kalakai, and young banana), and the formulated samples were tested. Formula A was 55 (cassava) : 5 (kalakai) : 40 (banana); formula B was 57:3:40; and formula C was 59:1:40. Those three formulations were compared with a control which was made from cassava nagara flour and banana flour with ratio of 60% and 40% (without kalakai). The results showed that the best formula was the A formulation, with a ratio content of 55:5:40. This formula had 0.90 g/ml of kamba density, 2.04 of water absorption index, 6.62% of moisture content, 3.02% of ash content, 0.67% of fat content, 2.41% of crude protein, and 4.48 mg/100g of Fe level.